Evangelical Paideia Overlooking the Pacific Rim: On the Opportunities and Challenges of Globalization for Christian Higher Education - Yong, Amos (Christian scholar's review, 2013)
What does it mean to do Christian higher education in global context? More specifically, what does this entail for specifically evangelical projects in higher education? Part of the answer to this question involves engaging in dialogue with non-Western traditions of education. This essay by Amos Yong is motivated by the challenges and possibilities attending such conversations and provides a case study exploring how East Asian educational philosophies, in particular those informed by the long history of Confucian educational models and practices, are conducive for a globally engaged evangelical approach to higher education. Yong looks specifically at educational goals and pedagogical strategies for an evangelical Paideia overlooking the Pacific Rim.